Fuzzy logic control mechanism for flash flood monitoring station - Supamit Jankoo (2018)
This paper proposes an adaptable flash flood monitoring station, called (MixKey). MixKeys have been designed, implemented, and installed on the target area. In order to efficiently operate under the real environmental conditions, fuzzy logic control mechanism has been applied to the design. This makes MixKey to automatically adapt its operation parameters (e.g., data transmission rate and electric power source) against the environmental condition changes. The results show that the fuzzy logic control mechanism contributes to reduce the RMS Error of the sensing data to the real-time environmental data with efficient battery consumption. © 2014 IEEE.